Response Assessment after Neoadjuvant Chemoradiotherapy in Rectal Cancer - Chandramohan, Anuradha; Augustine, Antony; Hiriyanna, Sneha; Natarajan, Shobiga; Selvam, Ajeet A.; Eapen, Kurian C.; Yadav, Saloni A.; Paul, Joseph Chacko; Lakhani, Aisha; Simon, Betty; Eapen, Anu (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Management of locally advanced rectal cancer is complex, and magnetic resonance imaging (MRI) findings play a central role in treatment decisions. While neoadjuvant chemoradiotherapy significantly improved local recurrence rates, newer treatment modalities, such as total neoadjuvant chemotherapy, improved distant control. They significantly improved pathological complete response rates, enabling organ preservation in more patients. MRI is the best imaging modality to assess treatment response. MRI aids in assessing operability, predicts surgical outcomes following neoadjuvant treatment, and aids in identifying patients' eligible for organ preservation and their follow-up. In this review, we discuss imaging techniques and interpretation of rectal cancer MRI following neoadjuvant treatment, provide a structured reporting template for response assessment MRI, and detail how imaging findings influence treatment decisions.
Keywords: MRI; rectal cancer; MDT; restaging; neoadjuvant chemoradiotherapy